Pendekatan Integratif dalam Filsafat Ilmu Penelitian Pendidikan - Ndanda Ambarawadi; Agus Zaenul Fitri (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2026)
A study of the philosophy of educational research shows a shift in paradigm from a single approach to an integrative approach that tries to combine scientific rationality, reflective meaning-making, and ethical values. This research aims to examine the conceptual development, paradigm foundations, and implications of applying an integrative approach in the philosophy of educational research during the period 2010–2025. The method used is a Systematic Literature Review (SLR) by analyzing 15 articles from reputable national and international journals. The review process includes stages of identification, screening, quality assessment, and thematic synthesis based on three main research questions. The results show that the integrative approach has developed from paradigm pluralism toward an epistemological synthesis that combines empirical, interpretive, critical, and spiritual elements. In a broad sense, this approach is based on a pluralistic ontology, a synthetic epistemology, and a humanistic–spiritual axiology that values meaning and significance as part of the construction of knowledge. You can see its practical implications in the emergence of reflective research designs like transformative mixed methods and Islamic integrative frameworks, which aim to balance scientific knowledge with human values. So, this integrative approach plays an important role in developing an educational research philosophy that’s more inclusive, reflective, and relevant to today’s social–spiritual context. Keyword : Philosophy of Science, Integrative Approach, Research Paradigm